UVIT Observations of the Small Magellanic Cloud: Point-source Catalog - A. Devaraj; P. Joseph; C. S. Stalin; S. N. Tandon; S. K. Ghosh (The Astrophysical Journal, 2023)
Three fields in the outskirts of the Small Magellanic Cloud were observed by the UltraViolet Imaging Telescope (UVIT) on board AstroSat, between 2017 December 31 and 2018 January 1. The observations were carried out on a total of seven filters, three in the far-ultraviolet (FUV; 1300–1800 Å) band and four in the near-ultraviolet (NUV; 2000–3000 Å) band. We carried out photometry of these observations that have a spatial resolution better than 1.″5. We present here the first results of this work, which is a matched catalog of 11,241 sources detected in three FUV and four NUV wavelengths. We make the catalog available online, which would be of use to the astronomical community to address a wide variety of astrophysical problems. We provide an expression to estimate the total count rate in the full point-spread function of UVIT that also incorporates the effect of saturation.